Marine Mammals in Sarawak - Cindy, Peter (Malaysian Nature Society, Kuala Lumpur, 2022)
They are not migratory. They are residents. They are here in Sarawak and they live here. Who are they, you may wonder? Well they are dolphins, whales and porpoises! Yes, we have these charismatic marine megafaunas in our waters and they live here year-round. According to the most updated count of cetacean species, there are 21 species in Sarawak. These include the large whales such as the Bryde’s and Humpback whales, to the smaller Irrawaddy Dolphins and Indo-Pacific Finless Porpoises (referred to from now on as the finless porpoise) (Ponnampalam, 2012). This article will focus on the species more commonly occurring in the coastal waters; where water enthusiasts, such as anglers and local fishermen, as well as the public might catch a glimpse of.